PENGARUH PERBEDAAN TEMPORER ANTARA LABA AKUNTANSI DENGAN LABA KENA PAJAK TERHADAP PERTUMBUHAN LABA KE DEPAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2010-2012) - Niko Ariston Depari; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of temporary differences between accounting income and taxes income for future earning growth. The independent variable of this study is deductible temporary differences and taxable temporary differences, the dependent variable is future earning growth, and the control variable are size and leverage. Deductible temporary differences measured by total deductible temporary differences divided by total assets. Taxable temporary differences measured by total taxable temporary differences divided by the total assets. Size measured by logarithm of total assets, and leverage measured by total long-term debt divided by total assets. While this study is the dependent variable future earnings growth as measured by the percentage of profit growth in the coming years. Sample of this study consists of 432 companies from manufacturing sectors listed on Indonesia Stock Exchange in 2010-2012. Samples were selected using purposive random sampling method with certain criteria, and gained as much as 156 companies that meet the criteria. The analysis technique is multiple regression analysis.Results of the analysis showed that the variable deductible temporary differences significant positive effect on future earnings growth and taxable temporary differences significant negative effect on future earnings growth. Based on these results mean future earnings growth is affected temporary differences.